THE CHECKS AND BALANCES DOCTRINE IN PROSECUTION OF MIXED MILITARY CRIME IN INDONESIA - Andhy H. Bolifaar (Scientia Integritas Utama, 2022)
Members of the military as part of society have potential in terms of mixed military crimes, namely crimes committed by unscrupulous members of the active military whose offenses occur within the scope of civil society in Indonesia. Based on the doctrine of checks and balances which embodies civilian supremacy, the prosecution of active military personnel who commit mixed crimes is carried out by military administrators whose control remains with the Attorney General of the Republic of Indonesia.